Professional military education in the South African national defence force : the role of the military academy - Esterhuyse, Abel Jacobus (Stellenbosch : University of Stellenbosch, 2011)
340 leaves printed on single pages, preliminary pages i-xvii and numbered pages 1-322. Includes bibliography, table of contents, list of figures, list of tables, list of abbreviations.